FACTORS AFFECTING CONSUMER PURCHASE DECISION ON INSURANCE PRODUCT IN PT. PRUDENTIAL LIFE ASSURANCE MANADO - Esau, Eko Yiswa Rasti (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Marketing Mix is the main factor that could affect the whole marketing system. The absence of marketing mix analysis will affecting negatively on a marketing performance. The research aims to analyze the influence of Product, Price, Promotion, People and Process of the Prudential Life Assurance Manado Area on the Consumer Purchase Decision. Data collected through distribution of questionnaires to 100 consumer of Prudential Life Assurance Manado Area. The research used Classic Assumption test and MultipleÂ  Regression analysis, to verify and to prove the research hypothesis. Analysis result shows that product, price, promotion, people and process simultaneously affect the consumer purchase decision. The result shows that Promotion variable has the most significant influence and People variable has the weakest influence in consumer purchase decision. The company is expected to keep the good performance on the promotion strategies, and maximize the performance on other variable, especially in people variable, in this case employee, and every person who involve in product and service production. Keywords: marketing, consumer behavior, consumer purchase decision, life insurance Â